(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Elastography is an imaging technique which has been used in the last decades and its role in breast masses characterization is well established. However, its value for predicting breast cancer grading is yet to be studied. Objective: To determine the role of strain elastography in the prediction of the grade of mammary ductal carcinoma. Methods: A cross sectional study enrolled 44 female patients with Breast Imaging Reporting and Data System (BI-RADS) Category 5 breast mass. Complete B-mode and elastographic ultrasound examination of the breast was performed with evaluation of the elastoscore and strain ratio. Correlation with the detailed histopathological report was done for cases that were proved to be ductal type breast carcinoma. Results: Significant correlation was found between the speculated outline of the tumor and grade III tumor (p=0.03). Breast tumors with higher Elastography/B mode size ratio (>1) and with high elasticity score (score 5) were significantly associated with grade III (p=0.02). The mean strain ratio of masses was significantly higher among grade III breast tumors (p